Persepsi mahasiswa teologi IAKN Tarutung Tentang LGBT - Rinaldi J K Lumban Toruan; Rahul Sihombing; Paramita Rosadi Hutagalung (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This research reviews Christian theological views towards LGBT, highlighting the conflict between religious beliefs and tolerance towards the LGBT community. In the context of theology students, there are interesting differences of opinion around this issue, with some opposing and others supporting. Nevertheless, this research emphasizes the importance of avoiding judgmental and condemnatory attitudes, and encouraging theology students to become agents of change who promote inclusion and understanding of LGBT people in society. Given the complexity of the views expressed, this article provides in-depth insight into how Christian theology and theology students interact with LGBT issues.